Study of Acetic Acid Percentages in Natural Herbicide for Weed Control - Mat Sani, Hisyamuddin; Muhammad Fairul Izwan Mohd Fazil; Abdul Rahman, Misbahul Muneer (Multidisciplinary Applied Research and Innovation, 2022)
Inorganic herbicides mostly used toxic ingredients such as cyanide. It is different from organic herbicides where the material used is less toxic and safe to use such as vinegar with a low percentage of acetic acid. Mixture of vinegar and other ingredients such as oil and soap is very effective in killing weeds in an instant. Acetic acid destroys plant tissue through contact action. The first objective in this study is to determine acetic acid percentage to control weeds in residential area. The second objective of this study is to study the cost effectiveness organic herbicides. Titration was carried out between vinegar and NaOH to determine the acetic acid percentage in vinegar. The average value of acetic acid found is 4.9%. Eight herbicides with different acetic acid percentages were prepared by adding with either 2 mL of soap or 2 mL of oil. Then tap water was added so that the total volume of mixture (vinegar, oil/soap, and water) will become 500 mL. Then spraying were done on three weed types selected for this study. The result shows, that organic herbicides with 1-2% acetic acid gives high percentage of weed killed (more than 90%) using the lowest cost only at RM 1.52 and RM 1.73 per 500 mL mixture.